Focused Ethnography of Diagnosis in Academic Medical Centers. Issue 10 (25th April 2018) - Chopra, Vineet; Harrod, Molly; Winter, Suzanne; Forman, Jane; Quinn, Martha; Krein, Sarah; Fowler, Karen E.; Singh, Hardeep; Saint, Sanjay
Abstract : BACKGROUND: Approaches of trainees to diagnosis in teaching hospitals are poorly understood. Identifying cognitive and system‐based barriers and facilitators to diagnosis may improve diagnosis in these settings. METHODS: We conducted a focused ethnography of trainees at 2 academic medical centers to understand the barriers and facilitators to diagnosis. Field notes regarding the diagnostic process (eg, information gathering, integration and interpretation, working diagnosis) and the work system (eg, team members, organization, technology and tools, physical environment, tasks) were recorded. Following observations, focus groups and interviews were conducted to understand the viewpoints, problems, and solutions to improve diagnosis. RESULTS: Between January 2016 and May 2016, four teaching teams (4 attendings, 4 senior residents, 9 interns, and 12 medical students) were observed for 168 hours. Observations of diagnosis during care led to identification of the following four key themes: (1) diagnosis is a social phenomenon, (2) data necessary to make diagnoses are fragmented, (3) distractions interfere with the diagnostic process, and (4) time pressures impede diagnostic decision‐making. These themes suggest that specific interventions tailored to the academic setting such as team‐based discussions of diagnostic workups, scheduling diagnostic time‐outs during the day, and strategies to "protect" learners from interruptions might prove to be useful in improving the process of diagnosis. Future studies that implement these ideas (either alone or within a multimodal intervention) appear to be necessary. CONCLUSION: Diagnosis in teaching hospitals is a unique process that requires improvement. Contextual insights gained from this ethnography may be used to inform future interventions.